2015
DOI: 10.1080/01446193.2015.1077981
|View full text |Cite
|
Sign up to set email alerts
|

Project manager-to-project allocations in practice: an empirical study of the decision-making practices of a multi-project based organization

Abstract: Empirical studies that examine how managers make project manager-to-project (PM2P) allocation decisions in multi-project settings are currently limited.Such decisions are crucial to organizational success. An empirical study of the PM2P practice, conducted in the context of Botswana, revealed ineffective processes in terms of optimality in decision-making. A conceptual model to guide effective PM2P practices was developed. The focus of this study is on deploying the model as a lens to study the PM2P practices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Considering the fact that lots of sources used in the literature review have suggested a possible link between project managers' age and project success, these results are startling. Seboni and Tutesigensi (2015) stated that project manager's age was a criteria used in during the selection process. Dulaimi and Langford (1999) noted that performance was impacted by age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering the fact that lots of sources used in the literature review have suggested a possible link between project managers' age and project success, these results are startling. Seboni and Tutesigensi (2015) stated that project manager's age was a criteria used in during the selection process. Dulaimi and Langford (1999) noted that performance was impacted by age.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, we need to distinguish between 'age' and 'experience' (Kulik et al, 2014). However, businesses hesitate about expressing anything about age during the employment process or choosing project team members for projects (Seboni and Tutesigensi, 2015). For instance, age may have an influence in choosing project managers however, it may not be explicitly mentioned because of a potential breach of employment laws and the risk of litigation (Seboni and Tutesigensi, 2015).…”
Section: Project Manager's Agementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, selecting and assigning them to the project as an HRM task is crucial for projects, while the role of HR managers in this process is unclear. To investigate how decisions on allocating project managers to projects are made and affect project performance, Seboni and Tutesigensi (2015) address the decision-making process of allocating project managers to projects in a project-based setting. The authors examine Seboni and Tutesigensi (2014) conceptual framework of allocating project managers to projects in Botswana.…”
Section: Project Managers and Project Performancementioning
confidence: 99%
“…The developer who controls financial, social and knowledge resources has access to decision power to influence project process, decision and performance. The literature of AHP decision analysis covers a complex project ecology of land and buildings: construction project or risk management (Preece et al , 2016; Seboni and Tutesigensi, 2015; Raisbeck and Tang, 2013; Doloi, 2008; Cheng and Li, 2004); investment, financing and valuation rationales (Wu et al , 2017; Hsieh, 1997); asset facilities management (Chadawada, 2015, Hardie and Newell, 2011); planning policy evaluation (Mosadeghi et al , 2015; Cay and Uyan, 2013; Bahadur and Yuji, 2008); and complex asset, e.g. brownfield, public and heritage evaluation (Wu and Kou, 2016; Wu et al , 2017; Kutut et al , 2014).…”
Section: Ahp Evaluation For Developer Decisionmentioning
confidence: 99%